Evaluasi Kinerja Instalasi Pengolahan Air Limbah (IPAL) PT. Wahana Kreasi Hasil Kencana (WKHK) Tangerang - Yoga Bangun Nugroho; Anie Yulistyorini; Mujiyono Mujiyono (Jurnal Teknologi Lingkungan, 2022)
Industry in Indonesia is currently increasing both in terms of technology and diversity. However, industries ocated near the rivers tends to dispose of their wastewater into the river bodies which causes water pollution. PT. Wahana Kreasi Hasil Kencana (PT KHK) Tangerang is a metal coating industry that produces heavy metal wastewater. The wastewater has been processed in the wastewater treatment plant (WWTP) but has not met the discharge standard yet. The study aims to examine the process performance of wastewater treatment in an existing condition and in the addition of a biochemical oxidation process. The results showed that the existing a lower concentrations of Pb, TSS, Ni, Zn, Cu, BOD, and COD. While the addition of biochemical oxidation process by adding microorganisms (Microplus) revealed high effectivity in decreasing the concentration of the wastewater. The addition of microorganisms into WWTP proved that heavy metal concentration in the effluent was removed. The efficiency of the removal was 78%, 63%, 80%, 61%, 78%, 62% and for Ni, Zn, CN, Cu, Pb, and BOD respectively, but the COD removal was approximately COD 53%. Furthermore, statistical analysis showed that pH has also influenced the removal of BOD and TSS up to 95.3% and 75.6% respectively, while Ni, Zn, Cu, and Pb concentration was not affected by pH.